Enhancing Social Skills of Young Children With ADHD: Effects of a Sibling-Mediated Intervention. Issue 5 (September 2020) - Daffner, Molly S.; DuPaul, George J.; Kern, Lee; Cole, Christine L.; Cleminshaw, Courtney L.
Children with attention deficit/hyperactivity disorder (ADHD) are at risk for experiencing problems with social functioning that are associated with adverse outcomes in adolescence and adulthood. To date, the most common ADHD treatments for children, psychostimulants and adult-mediated interventions, have had limited success reducing social impairments associated with ADHD. Using a non-concurrent multiple baseline across participants design, we examined the efficacy of a sibling-mediated social intervention for reducing negative and increasing positive social behaviors of three children with ADHD. We also assessed implementation integrity by the siblings, and acceptability from the perspective of the participant with ADHD, the siblings, and the parents. Results indicated that siblings learned and used specific social skills strategies with their siblings with ADHD that lead to increases in sharing, helping, and compromising behaviors for children with ADHD compared with baseline (Tau- U = 0.9531, p < .001). Summary of findings, study limitations, implications for research, and practice are discussed.